The facilitated cathodic elementary reactions of solid oxide electrolysis cells for CO2 conversion over a Ce decorated La0.43Ca0.37Ti0.94Ni0.06O3−δ electrocatalyst. Issue 38 (9th September 2022) - Li, Zhishan; Peng, Meilan; Zhu, Yinlong; Hu, Zhiwei; Pao, Chih-Wen; Chang, Yu-Chung; Zhang, Yifan; Zhao, Yingru; Li, Jianhui; Sun, Yifei
Abstract : Compared to LCTNi cathode, LCTNi-Ce exhibits better electrochemical performance in CO2 -SOEC with CO or H2 as the protective gas. Abstract : A high temperature solid oxide electrolysis cell is recognized as a promising technology for CO2 conversion (CO2 -SOEC). The development of alternative cathode materials substituting conventional Ni/YSZ is a great challenge for SOECs, on which multi-step elementary reactions ( e.g., adsorption of CO2, conversion of reaction intermediates, and desorption of CO) occur in succession. Herein, the Ce decorated La0.43 Ca0.37 Ti0.94 Ni0.06 O3− δ perovskite (denoted as LCTNi-Ce) is synthesized and applied as a potential cathode electrocatalyst for a CO2 -SOEC. The in situ exsolution strategy and A-site deficiency enable the surface decoration of plenty of Ni nanoparticles (NPs) serving as efficient reactive sites. Furthermore, the Ce decoration leads to increased oxygen vacancy concentration, accelerated oxygen exchange rate and improved CO desorption capacity. The symmetrical half-cell measurement confirmed the boosted electrolysis performance in both CO2 /CO and CO2 /H2 atmospheres. DRT analysis further evidences the facilitated oxygen ion transportation and gas adsorption/dissociation upon Ce decoration. Compared to a LCTNi cell, the LCTNi-Ce cell exhibits a significantly promoted current density of −0.557 A cm −2 in 50% CO2 /50% H2 at 800 °C and 1.3 V, and a reduced R p value of 0.514 Ω cm −2 under OCV condition.